Examining self-described policy-relevant evidence base for policymaking: an evidence map of COVID-19 literature - Chukwu, Emelda E (2024)
Background: Evidence-basedpolicymaking is a paradigmaimed at increasing the use of evidence by actors involvedin policymaking processes. The COVID-19pandemichighlighted a heavy reliance on emerging evidence forpolicymaking during emergencies.Objective This study describes the focus and types ofevidence in journal articles self-describedas relevant topolicymaking using the COVID-19pandemic as a casestudy, identifying gaps in evidence and highlighting authorstated perceived biases specifically in evidence-basedpolicy making.Design Evidence mapping.Data sources We systematically searched SCOPUS,PubMed and LexisNexis for literature identifying policy-relevantevidence available on the COVID-19pandemic.Eligibility criteria The study included only peer-reviewedliterature identified as ‘article’, ‘book chapter’, ‘review’covering the period from January 2020 to December 2022.Inclusion criteria required that articles have an abstract,authorship attribution and are written in English.Data extraction and synthesis A minimum of twoauthors independently extracted and coded for every leveland final outputs were compared for consistency.Results A total of 213 articles met the inclusion criteriaand were reviewed in this study. Lead authorshipaffiliations were from 50 countries with 70% of the outputsfrom developed economies including USA (20.2%), UK(18.3%) and Australia (7.5%). The most common purposeof the articles was the presentation of research findingsthe authors considered of relevance to policy (60.1%),followed by work that examined the impact of policy(28.6%) or highlighted or supported a policy need (22.5%),while some papers had multiple stated purposes. Themost common challenges in policymaking identified by theauthors of the reviewed papers were process failures andpoor evidence utilisation during policymaking.Conclusions The evidence map identified the need foran interdisciplinary policy approach involving relevantstakeholders and driven by quality research as aprogressive step towards prevention of future public healthcrises/pandemics.